The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/rs13163092
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Variability of Tropospheric Ozone over Oceania and Southern Pacific during the 2019–20 Australian Bushfires

Abstract: The present study contributes to the scientific effort for a better understanding of the potential of the Australian biomass burning events to influence tropospheric trace gas abundances at the regional scale. In order to exclude the influence of the long-range transport of ozone precursors from biomass burning plumes originating from Southern America and Africa, the analysis of the Australian smoke plume has been driven over the period December 2019 to January 2020. This study uses satellite (IASI, MLS, MODIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
(189 reference statements)
0
2
0
Order By: Relevance
“…The 2019/2020 Australian fires resulted in a vast injection of CO 2 into the atmosphere (Byrne et al, 2021;van der Velde et al, 2021) and record-breaking aerosol optical depth levels in the Southern Hemisphere, with smoke injection into the stratosphere comparable to a volcanic eruption that impacted dynamical circulation and radiative balance (Khaykin et al, 2020;Fasullo et al, 2021;Hirsch and Koren, 2021). The fires had significant impacts on tropospheric composition including elevated CO and ozone over the Oceania and southern Pacific regions (Be `gue et al, 2021;John et al, 2021) as well as deposition into the Southern Ocean resulting in widespread phytoplankton blooms (Tang et al, 2021). Smoke from the fires caused some of the worst air pollution events on record in Australia, with large populations exposed to hazardous air quality over extended periods of time (Nguyen et al, 2021).…”
Section: Impacts Of Fire Emissions On Atmospheric Chemistrymentioning
confidence: 99%
“…The 2019/2020 Australian fires resulted in a vast injection of CO 2 into the atmosphere (Byrne et al, 2021;van der Velde et al, 2021) and record-breaking aerosol optical depth levels in the Southern Hemisphere, with smoke injection into the stratosphere comparable to a volcanic eruption that impacted dynamical circulation and radiative balance (Khaykin et al, 2020;Fasullo et al, 2021;Hirsch and Koren, 2021). The fires had significant impacts on tropospheric composition including elevated CO and ozone over the Oceania and southern Pacific regions (Be `gue et al, 2021;John et al, 2021) as well as deposition into the Southern Ocean resulting in widespread phytoplankton blooms (Tang et al, 2021). Smoke from the fires caused some of the worst air pollution events on record in Australia, with large populations exposed to hazardous air quality over extended periods of time (Nguyen et al, 2021).…”
Section: Impacts Of Fire Emissions On Atmospheric Chemistrymentioning
confidence: 99%
“…They showed that the tropospheric ozone reaches its maximum partial column (45 DU), and its highest ozone mixing ratio during spring (October), coinciding with the BB season, with impacts on the change of surface UV radiation by up to 10%. Bègue et al (2021) [10] examined the transport and variability of tropospheric ozone across Oceania and the South Pacific during the 2019-2020 Australian bushfires, demonstrating how major BB events affect tropospheric trace-gas abundance, particularly ozone, on a regional scale. Moreover, Khaykin et al (2020) [11] reported that these Australian bushfires spread over longer distances, with planetary-scale repercussions.…”
Section: Introductionmentioning
confidence: 99%